Topographic associations of hyperreflective materials in diabetic retinopathy: a multimodal correlation with microvascular pathology, structural remodeling and systemic metabolic dysregulation - Zhou, Lan; Sun, Hongyan; Li, Cunzi; Luo, Tianyi; Meng, Ting; Wen, Xiaojun; Chen, Zilin; Hu, Yan; Yang, Ming-Ming (Frontiers in Medicine, 2025)
BackgroundHyperreflective materials (HRMs), enigmatic biomarkers observed in diabetic retinopathy (DR), exhibit poorly characterized pathophysiological origins and clinical implications.MethodsThis retrospective cross-sectional study investigates the spatial distribution patterns of HRMs subtypes and their integrative relationships with retinal microvascular architecture, structural remodeling, and systemic metabolic parameters in 205 DR eyes. HRMs were systematically classified via multimodal optical coherence tomography angiography (OCTA) analysis, incorporating topographic localization (inner vs. outer retinal), reflectivity profiles, morphometric dimensions, posterior shadowing artifacts, and decorrelation signal. Quantitative correlations were established between HRMs subtypes and OCTA-derived vascular parameters (intraretinal microvascular abnormalities [IRMA], non-perfusion [NP] areas, microaneurysms), diabetic macular edema (DME) status, and systemic metabolic indices (glycemic control, lipid profiles, renal function, inflammatory markers).ResultsSix distinct HRMs phenotypes were identified: inner retinal hyperreflective spots (IRHFs), outer retinal hyperreflective spots (ORHFs), intraretinal hard exudates (IRHE), outer retinal hard exudates (ORHE), decorrelation-positive HRMs, and cotton-wool spots. Spatial mapping revealed predominant HRMs colocalization with IRMA territories (75.4% IRHFs, 89.5% ORHFs, 90.8% IRHE, 94% ORHE), while 19% of IRHFs and 8.7% of ORHFs overlapped NP zones. Decorrelation-positive HRMs demonstrated dual associations with IRMA (77.6%) and microaneurysms (21.0%). DME eyes exhibited significantly elevated HRMs density within IRMA and NP regions (P < 0.001). Multivariate analysis identified dyslipidemia as a strong predictor of HRMs burden.ConclusionsThese findings establish HRMs as spatially resolved biomarkers of diabetic retinal pathophysiology, reflecting compartment specific interactions between microvascular incompetence (IRMA-associated barrier failure), ischemic remodeling (NP zones), and systemic metabolic dysregulation. The colocalization of HRMs subtypes with IRMA walls and leakage-prone microaneurysms supports their putative role as optical signatures of lipoprotein extravasation and inflammatory lipidotoxicity in DR progression.